Recidivism and concomitant criminality in pathological firesetters - Barnett, Winfried; Richter, Paul; Sigmund, Dieter; Spitzer, Manfred (Journal of forensic sciences, 1997)
The purpose of this study was to explore dangerousness and fire setting recidivism of mentally disordered firesetters in comparison with mentally healthy arsonists. In Germany, all trials are registered centrally by the Federal Central Register. The records of this Register for the three year period from 1983 until 1985 were used in this follow-up study of arsonists to identify three samples of subjects: (1) All persons convicted of arson who have been found not guilty by reasons of insanity (n = 186), (2) all person convicted of arson who have been found guilty of diminished responsibility (n = 97), and (3) a random selection from all persons convicted of arson who have had no psychiatric examination in their trial (n = 187). The follow-up ended in 1994, providing a period of, on average, ten years. Mentally disordered arsonists differed from non-mentally disordered arsonists in the following ways: They were more likely, first, to have a history of arson before 1983, and secondly, to be convicted of arson again (11% relapse compared to 4%). Mentally disordered arsonists had fewer registrations of common offenses, such as theft as well as traffic violations and alcohol-related offenses. Based on the present sample, mentally disordered firesetters have a higher rate of recurrence of firesetting than non-mentally disordered firesetters and commit fewer common offenses other than firesetting.
Gesehen am 09.12.2020